Qualidade do gasto público municipal em ensino fundamental no Brasil - Maria Dolores Montoya Diaz (Brazilian Journal of Political Economy, 2012)
Quality of municipal public spending on primary education in Brazil. The focus of this paper was to analyze the relationship between municipal public education spending and students' academic achievement, evaluated according to IDEB (Index of Basic Education Development) of 2005. The following databases were used: School Census 2005, Brazil Exam (mathematics evaluation applied to students from fourth grade of elementary school) and Finance of Brazil (FINBRA). A multilevel model was estimated and the results suggest that simply increasing the percentage of municipal expenditures on education or the percentage of spending on primary education in relation to municipal expenditures on education do not automatically guarantee improvements in the quality of education.